Die Nuwe Testament en mitologie: Die probleem van die ontmitologisering van die Nuwe-Testamentiese verkondiging. Bultmann se 1941-opstel weer bekyk - Malan, Gert J. (HTS teologiese studies, 2015)
In the Afrikaans-speaking South African theological context, there was little positive regard for Bultmann’s work, especially for his demythologising program. More than seventy years have passed since Bultmann’s 1941 essay on demythologising started a lively debate. For most, Bultmann and his legacy have receded into the past. With the 130th commemoration of Bultmann’s birthday this year, it seems appropriate to revisit his 1941 essay on demythologising. The purpose of this paper is to listen again to the voice of Bultmann, unhindered by the interpretations of his work by others. This is possible, as the dust has long settled after the demythologisation debate. This exercise may reveal that Bultmann’s work is still relevant in our new theological context.